Formulasi Sediaan Krim Ekstrak Etanol Buah Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) Dengan Basis Vanishing Cream Dan Uji Aktivitas Antibakteri Terhadap Staphylococcus epidermidis - Aulia Savitri, Annisa; , Dr. T.N. Saifullah S., M.Si., Apt; , Rima Munawaroh, M.Sc., Apt (2016)
Mahkota dewa fruits (Phaleria marcrocarpa (Scheff.)Boerl) is one of medicinal plants as a traditional medicine for acne. The ethanolic extract of Phaleria contained flavonoids and saponins as an antibacterial agent. This research aims to made cream with Phaleria fruit ethanolic extract and had to known of antibacterial activity cream against Staphylococcus epidermidis. Soxhletation method used to make ethanol extract of Phaleria fruit. The TLC and qualitative tests were used for test of containing extracts. The extract would be used to made cream with vanishing cream base and a comparison the proportion of tween 80 and span 80 as emulsifier. Then, cream was tested in an antibacterial activity and physical stability test used freeze-thaw cycling method. The results showed that the addition proportion of Tween 80 in the formula increase viscosity and adhesiveness, and lower spreadability. ANOVA test results on the physical properties of the cream obtained p-value 0.00 < 0.05, which mean a difference physical cream test were affected by differences in the concentration of emulsifier. The results of stability test cream with freeze-thaw cycling method showed that cream only stable until second cycle. Results of the test cream antibacterial activity had an irradikal diameter of bacterial inhibition zone Antibacterial test before and after freeze-thaw cycling had p-value >0.05, which means there's no effect of stability test on antibacterial activity.